Fertilização nitrogenada na produção de duas variedades de milho roxo cultivadas no sul do Brasil - Guevara, Mario Pedraza (2020)
In Brazilian agroecological systems, the use of Creole varieties in conventional systems is common. Purple corn is a cereal grown in the Inter Andean areas, but it can also be developed in the state of Paraná. Little is known about the behavior of these varieties in response to nitrogen fertilization levels. This work was carried out from October to January 2018/2019 in a production system located in the experimental area of UTFPR-Pato Branco, at coordinates 26º41'17 ”South and 52º41’17” west. The objective was to evaluate the agronomic components (height of the plant-AP; height of the insertion of the ear-EIA; length of the ear-CE; diameter of the ear-DE; number of grains per row-NGF; number of rows per ear- NFE; mass of 1000 grains-MMG; productivity-PROD) and some physicochemical components (total phenols-FT, antioxidant activity index-IAA and anthocyanins) of two varieties of purple corn (UNC-47 and INA-601), at the stage V4 with application of different doses of nitrogen (0; 50; 100; 150 kg ha-1), using urea (46%) as a source. The experimental design was randomized blocks, with four replications. The results indicate that the variables AP, AIE, CE, DE, NGPF, NFPE, NGPE, PMS and PROD. respond positively in relation to the doses of N. In the evaluation of the nitrogenous organic components such as total phenols and antioxidant activity index of grains and cobs, there are expressive positive levels, in fractions of mg EAG / g. and DPPH inhibition, showing a significant correlation between the two variables. However, nitrogen fertilization, for total monomeric anthocyanins (cy- 3-glu / g), promoted the decrease and interfered in an antagonistic way in the quality of the synthesis of anthocyanin pigments in purple corn.